(untitled) (CAHIERS MAGELLANES-NS, 2024)
The micro, small, and medium-sized firm (MSME) sector in India consistently demonstrates remarkable viability despite challenging economic circumstances, both at the global and domestic levels. With increasingly fierce competition, it is important for MSMEs to understand the factors that influence employee retention, one of which is the level of job satisfaction. Job satisfaction is an important indicator of the relationship between employees and the organizations where they work. When employees feel satisfied with their work, they tend to be more motivated, productive, and have a higher level of loyalty to the company. On the other hand, job dissatisfaction can potentially cause employees to look for new job opportunities, which in turn can affect organizational stability and performance Therefore, research on the influence of job satisfaction on employee retention is relevant. By understanding this relationship, management can take appropriate steps to increase employee job satisfaction and ultimately increase their retention, which in turn will have a positive impact on the performance and overall success of MSMEs.